ACADEMIC COMMUNICATION IN THE SYSTEM OF PROFESSIONAL LECTURE TRAINING OF FUTURE TEACHERS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines academic communication as a crucial component of professional lecture training for future teachers. It analyzes contemporary scientific approaches to developing teachers' communicative competence, the culture of public and academic speaking, and the skills of organizing dialogue, discussion, and facilitating the learning process in a digital educational environment. Drawing on the work of international and domestic researchers, the role of academic communication in developing lecture skills, professional thinking, and pedagogical interaction is explored. The need for targeted inclusion of communicative and rhetorical training in the professional education of future teachers is substantiated.